Best answer:
You can cancel two opposites since a number divided by its opposite = -1.
[-2x/(x² - 1)].[(1 - x²)/2] The -2 and 2 cancel to -1 and 1, and the (x² - 1) cancels the (1 - x²) to be -1 and 1 so you'd get
(-1)(-1)x = just x
You could also look at it like this: (1 - x²) = -1(-1 + x²) by reverse distributive then...
show more
Best answer: You can cancel two opposites since a number divided by its opposite = -1.
[-2x/(x² - 1)].[(1 - x²)/2] The -2 and 2 cancel to -1 and 1, and the (x² - 1) cancels the (1 - x²) to be -1 and 1 so you'd get
(-1)(-1)x = just x
You could also look at it like this: (1 - x²) = -1(-1 + x²) by reverse distributive then by commutative it = -1(x² - 1)
and now cancel the (x² - 1)'s directly.
Or With just numbers, for example, (8 - 3) / (3 - 8) = -1 from canceling, and if you did it out you have 5 / (-5) which is -1
8 answers
·
17 hours ago